(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This report is based on Palhaçaria de Terreiro and Corpo-Mandinga pedagogies, developed in order to deconstruct and decolonize pre-established standards in the clowning language, and in order to include Afro-diasporic, Afro-indigenous and Capoeira Angola knowledge on these practices. Therefore, the report aims at presenting clowning from a black culture perspective, in which spirituality and clowning are integrated to create a clown. Firstly, the creation of masks is discussed here, from my personal experiences. Secondly, we approach the steps of this creation, based on my artistic and teaching experiences. Finally, we can observe that Palhaçaria de Terreiro and Corpo-Mandinga pedagogies allow participants to recuperate their ancestry and to discover other ways to express themselves.